An investigation into serotonergic and environmental interventions against depression in a simulated delayed reward paradigm. (August 2020) - Porr, Bernd; Miller, Alice; Trew, Alex
The disruption of the serotonergic (5HT) system has been implicated in causing major depression and the standard view is that a lack of serotonin is to blame for the resulting symptoms. Consequently, pharmacological interventions aim to increase serotonin concentration in its target areas or stimulating excitatory 5HT receptors. A standard approach is to use serotonin reuptake inhibitors (SSRIs) which cause a higher accumulation of serotonin. Another approach is to stimulate excitatory serotonin receptors with psychedelic drugs. This article compares these two approaches by first setting up a system-level limbic system model of the relevant brain areas and then modelling a delayed reward paradigm which is known to be disrupted by a lack of 5HT. Central to our model is how serotonin changes the response characteristics of decision-making neurons where low levels of 5HT allow small signals to pass through, whereas high levels of 5HT create a barrier for smaller signals but amplifying the larger ones. We show with both standard behavioural simulations and model checking that SSRIs perform significantly better against interventions with psychedelics. However, psychedelics might work better in other paradigms where a high level of exploration is beneficial to obtain rewards.